Brain activation and adaptation of deception processing during dyadic face-to-face interaction. (November 2019) - Tang, Honghong; Zhang, Shen; Jin, Tao; Wu, Haiyan; Su, Song; Liu, Chao
Abstract: Though deception is consistently characterized by the slippery-slope effect, i.e., the escalation of small lies over time, differing interactive situations and interacting processes may influence the trajectories of deception. To explore this influence, we investigated naturalistic face-to-face (FF) and computer-mediated face-blocked (FB) interactions using functional near-infrared spectroscopy (fNIRS). Pairs of participants acted as deceivers and receivers in an adapted ultimatum game while brain activity in the right dorsolateral prefrontal cortex (rDLPFC) and temporoparietal junction (rTPJ) was recorded. Comparison of deception in the two types of interactions showed that the FF interactions resulted in more successful deception, as well as acceptance of deception, and prompted more neural activation in the rDLPFC than the FB interactions. We found that the deception magnitude escalated in both FF and FB interactions, but rDLPFC activity during deception diminished over time only in the FF interactions but not in FB interactions, suggesting that the deceivers behaviourally adapted to deception over time in both types of interactions, but the neural adaptation occurred only in the FF interactions. Furthermore, neural adaptation in FF interactions was associated with behavioural switching after deception, indicating that the rDLPFC contributes to deception adaptation and the control of switching between deception and honesty. The FF interactions were also characterized by activity in the rTPJ, which showed an adaptation to deception. These findings highlight the importance of interactive situations in dyadic naturalistic settings for deception and the role of the rDLPFC and rTPJ in the slippery-slope effect in deception.